ANALYSIS OF AIRBNB TAX POTENTIAL IN INDONESIA USING WEB-SCRAPED DATA AND HEDONIC PRICING MODEL - Aulia Rahman; Sartika Djamaluddin (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Since its inception in Indonesia in 2013, Airbnb has grown rapidly in several provinces, reaching a total of 72,721 listings by 2019. However, the Airbnb business in Indonesia remains unregulated, as operational and taxation studies are still underway. Based on this, this study aims to investigate the feasibility and calculate the potential of Airbnb hosts as a new source of tax revenue in Indonesia. Furthermore, this study also aims to identify factors influencing rental prices as a source of income for Airbnb hosts in Indonesia. The data used in this study were obtained from the Airdna website and web-scraping results on the Airbnb website, with a sample size of 628 listings. The descriptive analysis results indicate that Airbnb hosts can be considered as MSME tax objects, with an estimated potential tax revenue of IDR 359 million in 2019. The third finding indicates that the factors influencing Airbnb rental prices in Indonesia are location, accommodation type, and facilities.